Rationing nursing care and organizational factors in intensive care units. - Anna Antoszewska; Aleksandra Gutysz-Wojnicka (PLoS ONE)
Introduction Rationing nursing care is a term that applies to various aspects of the required patient care that are omitted or their performance is delayed. Aim This study aimed to identify the extent of rationing of nursing care in intensive care units (ICUs) in different types of hospitals and determine the relationship between rationing of nursing care and hospital and staff characteristics. Methods This quantitative, cross-sectional, multicenter study was performed. The sample comprised 226 nurses working in ICUs in a North-East part of Poland. The Polish version of the PRINCA questionnaire methods was applied. The survey was conducted between 15 January and 31 May 2023. Results There were statistically significant differences between rationing of nursing care in university/provincial hospitals and district hospitals t = 6.92 p<0.001. In provincial and university hospitals, nursing care is often omitted, leading to a lower perceived quality of nursing care (t = -3.0 p = 0.003). This is further compounded by the fact that nursing care is more likely to be rationed in units with a larger number of beds. The level of rationing of nursing care was significantly correlated with the perceived work quality and job satisfaction in both types of hospitals. The most frequently omitted aspects of nursing care included providing emotional support (university/provincial 1.27 vs. district 0.89), patient and family education (1.11 vs. 0.74), communication with external entities (1.11 vs. 0.84), and observing safe patient-handling practices (1.01 vs. 0.99). Conclusion The type of hospital and organizational factors influence the rationing of nursing care. Improvements in working conditions can improve nursing care quality in ICUs.